ANALISIS PENINGKATAN EKSISTENSI PROMOSI PEMASARAN PRODUK MEBEL/FURNITURE DI TENGAH PANDEMI COVID - 19 PADA UD. MABRUK MATARAM - Dewi Rispawati; Suryaningsih Suryaningsih (Jurnal Inovasi Penelitian, 2021)
This research is entitled “Analysis of Increasing Existence of Furniture Product Marketing Promotion Amid the Covid - 19 Pandemic at UD. Mabruk Mataram”, which aims to increase the existence of marketing promotions for furniture products in the midst of the Covid - 19 pandemic. This research is a descriptive study using the case method. Data collection techniques in this study are using observation, interviews and documentation. The type of data in this research is using qualitative data and quantitative data and the data sources in this study are primary data and secondary data. Based on the results of this research analysis to improve the existence of marketing promotion for furniture products in the midst of the Covid - 19 pandemic at UD. Mabruk Mataram can be done such as: placing advertisements through print and electronic media, posters and leaflets, through electronic shopping media, creating catalogs, sponsoring events, preparing professional employees, providing souvenirs, coupons with prizes and discounts/prices and holding events/entertainment activities for the surrounding community. Increasing the existence of furniture product marketing promotions in the midst of the Covid - 19 pandemic at UD. Mabruk Mataram, so that in the future it can continue to exist in the midst of the Covid - 19 pandemic in marketing furniture products so that it can increase sales volume and can satisfy consumers who buy furniture products at UD. Mabruk Mataram and can market UD. Mabruk Mataram furniture products to outside the area.